2008
DOI: 10.1063/1.3006439
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Seebeck coefficient studies of the electronic band structure in Nb1−xB2

Abstract: With the aim of providing experimental information for the Nb deficiency enhanced superconducting temperature (TC) in the Nb1−xB2 samples, we carried out a study on Nb1−xB2 (x=0, 0.13, 0.20, and 0.26) by means of nuclear magnetic resonance (NMR) and Seebeck coefficient (S) measurements. From the N93b NMR spin-lattice relaxation rates, we can deduce the Nb 4d partial Fermi level density of states (DOS) Nd(EF) for each individual composition. The result indicates that Nb0.74B2 and Nb0.80B2 possess large Nd(EF) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The specimen was put in a plastic vial that showed no observable 93 Nb NMR signal. 17 The 93 Nb NMR central transition lines were obtained by the Fourier transform of a half of the spin-echo signal using a standard π/2−τ − π sequence. Within the Re 24 Ti 5type crystal structure, there are two crystallographic Nb sites, Nb(1) and Nb(2), with population ratio of 1:4.…”
Section: Resultsmentioning
confidence: 99%
“…The specimen was put in a plastic vial that showed no observable 93 Nb NMR signal. 17 The 93 Nb NMR central transition lines were obtained by the Fourier transform of a half of the spin-echo signal using a standard π/2−τ − π sequence. Within the Re 24 Ti 5type crystal structure, there are two crystallographic Nb sites, Nb(1) and Nb(2), with population ratio of 1:4.…”
Section: Resultsmentioning
confidence: 99%
“…These properties are thought to arise from or at least be influenced by the boron bonding environments , found in these materials. As a result, numerous nuclear magnetic resonance (NMR) studies have been reported. , …”
Section: Introductionmentioning
confidence: 99%